Early opening of sarcolemmal ATP-sensitive potassium channels is not a key step in PKC-mediated cardioprotection. (February 2015) - Brennan, Sean; Jackson, Robert; Patel, Manish; Sims, Mark W.; Hudman, Diane; Norman, Robert I.; Lodwick, David; Rainbow, Richard D.
Abstract: ATP-sensitive potassium (KATP ) channels are abundantly expressed in the myocardium. Although a definitive role for the channel remains elusive they have been implicated in the phenomenon of cardioprotection, but the precise mechanism is unclear. We set out to test the hypothesis that the channel protects by opening early during ischemia to shorten action potential duration and reduce electrical excitability thus sparing intracellular ATP. This could reduce reperfusion injury by improving calcium homeostasis. Using a combination of contractile function analysis, calcium fluorescence imaging and patch clamp electrophysiology in cardiomyocytes isolated from adult male Wistar rats, we demonstrated that the opening of sarcolemmal KATP channels was markedly delayed after cardioprotective treatments: ischemic preconditioning, adenosine and PMA. This was due to the preservation of intracellular ATP for longer during simulated ischemia therefore maintaining sarcolemmal KATP channels in the closed state for longer. As the simulated ischemia progressed, KATP channels opened to cause contractile, calcium transient and action potential failure; however there was no indication of any channel activity early during simulated ischemia to impart an energy sparing hyperpolarization or action potential shortening. We present compelling evidence to demonstrate that an early opening of sarcolemmal KATP channels during simulated ischemia is not part of the protective mechanism imparted by ischemic preconditioning or other PKC-dependent cardioprotective stimuli. On the contrary, channel opening was actually delayed. We conclude that sarcolemmal KATP channel opening is a consequence of ATP depletion, not a primary mechanism of ATP preservation in these cells. Highlights: Opening of the SarcoKATP channel was proposed to be cardioprotective. Channel opening was delayed after cardioprotective stimuli. Ca 2+ & ATP levels were maintained during ischemia independent of SarcoKATP opening. Mitochondrial function was preserved during ischemia, independent of SarcoKATP opening. Early opening of SarcoKATP is not involved in PKC-dependent cardioprotection.